Pierced Pseudonymity: Vint Cerf Interview. (13th February 2019) - Runciman, Brian
Abstract: Vint Cerf is co-inventor of the internet and Google's Chief Internet Evangelist. He recently delivered the Romanes Lecture. Brian Runciman MBCS caught up with him afterward.